The dynamics of decay processes in rare plasma - Antonov, A.N.; Buts, V.A.; Koval’chuk, I.K.; Kovpik, O.F.; Kornilov, E.A.; Svichensky, V.G.; Tarasov, D.V. (Вопросы атомной науки и техники, 2009)
The results of the experimental and theoretical investigations of chaotic decay process of HF wave on two new − HF and LF wave in the cylindrical resonator filled with rare plasma are presented. The branches of oscillations which can participate in such process are specified. The possible mechanisms of appearance of burst of radiation which follows after certain time delay after the main impulse obtained in the experiment are discussed. The qualitative agreement of the theoretical deductions with the experimental results is observed.